THE MOST IMPORTANT EPOCHES OF PRECАMBRIAN OF UKRAINIAN SHIELD - SHCHERBAK, D.; MYKHAYLOV, V.; GRINCHENKO, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
There are six metallogenic epochs with special host rocks and ore formations in the Precambrian of the Ukrainian Shield: the Early (3.8–3.4 Ga), the Middle (3.4–3.1 Ga) and the Late Archean (3.1–2.6 Ga), the Early (2.6–2.1 Ga), the Middle (2.1–1.8 Ga), and the Late Proterozoic (1.8–1.6 Ga). The Late Archaean and the Middle Proterozoic epochs are the most favorable for the gold mineralization; the Early and Late Proterozoic epochs – for uranium; the Late Archean Belozersky (3,0-2,98 Ga) and Early Proterozoic Kryvorizka (2,3-2,1 Ga) and Frunzenska (near 2 Ga) stages was the more favorable for iron ores; and the Middle – Late Proterozoic epochs – for rare-metal mineralization.